Caring for Persons with Disabilities in the Light of the 2030 Sustainable Development Goals: A Case Study of the Policies of the Palestinian Ministry of Social Development - Taffal, Suha Zuhair (Journal of Educational and Psychological Sciences, 2021)
The purpose of this study is to analyze the reality of the Ministry of Social Development programs for persons with disabilities in the Palestinian society and to know the effectiveness and efficiency of these programs in assisting these people, enabling them to integrate into the Palestinian society and achieving social development. The study followed the analytical method and used interviews. It also reviewed related studies including reports and.The results indicate that the programs of the Ministry of Social Affairs target poverty, not disability, criterion. The cash assistance does not contribute to transferring the reality of relief services to development that the ministry aims through its various programs. This is not consistent with achieving the development goals set by the National Policy Agenda 2017- 2022 in fulfilling social justice and combating poverty. The study recommends developing procedures and future strategic policies in order to achieve development goals.
Keywords: Sustainable Development; Caring for Persons with Disabilities; Social development